Estudo teórico de sistemas de coordenação contendo vanádio(IV)/vanádio(V)/ácido acetoidroxâmico, alumínio /citrato e compostos de inclusão entre espironolactona e b-ciclodextrina - Antonio Luiz Oliveira de Noronha (2010)
The study of chemical reactions is certainly one of the most challenging and interesting fields within the chemical world. The understanding of the chemical reaction mechanism at a molecular level, determining its intermediates and products is still a challenge for the researchers. The investigation of the different chemical species involved in a chemical reaction, their geometric structure and their electronic and thermodynamic properties is the first step for understanding chemical reactivity. In aqueous solution the mechanism of the chemical reaction becomes even more complex since water molecules coordinated at metal ions centers can hydrolyze, and change the predominant conformation/ tautomer through the acid/base reactions. Theoretical chemistry has tools that allows to investigate the chemical processes estimating the thermodynamic and electronic properties of chemical species and contributing for the understanding of complex systems. In this thesis, the density functional theory was used to investigate three different systems in which the chemical speciation is very important.The first system studied was the oxide-reduction process of the V(IV)/V(V) ions in the presence of acetohydroxamic acid in aqueous solution. The study of this system is important for understanding the mechanism of action of the haloperoxidase class of enzymes. This system serves as a model for the active site of these enzymes. Furthermore, the complexation of acetohydroxamic acids provides also information about the coordination of vanadium with proteins. The mechanism of reaction was investigated and the various intermediates calculated. For the global reaction of oxidation, the reaction energy were estimated in 40,4 kcal.mol-1, with an error of -1,5 kcal.mol-1 in relation to the knownexperimental value. This error correspond to 2,4 logarithmic unit in the log (b), that is, presents an error similar to the error bars of the experimental results if one takes into account the medium. The second system was the coordination between aluminum ion and the citrate anionin aqueous solution. This system presents a complex equilibrium involving several chemical species, with some polymeric species and others that, even seeming simplicity, proved to be an interesting challenge. A 1:1 neutral species was the object of several studies in the last years, including theoretical investigations. However, even with all the available information there was not a proposal of a chemical species that was in good agreement with all experimental and theoretical results available. The model proposed in the present thesis is in good agreement with the experimental results and presents a deviation from the experimental results of only 2,4 kcal.mol-1. The last system studied was the inclusion compound between the spironolactone andthe -cyclodextrin. In this last work the main goal was to provide information to support the results found using some modern NMR techniques, and prove that the inclusion actually happened. Furthermore, the predicted values show excellent agreement with the NMRresults and so it was possible to show that when different processes for obtaining the inclusion complex is used, for this system, two different species are formed, according to the employed system. This system is in the limit of the utilization of theoretical method due to the its size and the fact the intermolecular interactions have an important role. Therefore, it was used an approximate method of the DFT the SCC-DFTB method to describe the system of inclusion. This is the first work that this method was used for describing the inclusion compounds. The chemical speciation study is, without question, one of the more challenging andinteresting subjects in chemistry nowadays, and, using techniques of modern theoretical chemistry, in special the density functional theory, important information can be obtained about the species involved in a particular reaction, their geometrical, thermodynamic and electronic properties. This thesis contributes to enlarge the utilization of theoreticaltechniques in the investigation of complex chemical system in aqueous solution contributing for the interpretation of the experimental results and in the understanding of the reaction chemistry mechanism at a molecular level